Supercapacitor Performance of Magnetite Nanoparticles Enhanced by a Catecholate Dispersant: Experiment and Theory - Coulton Boucher; Oleg Rubel; Igor Zhitomirsky (Molecules, 2023)
The full potential of Fe3O4 for supercapacitor applications can be achieved by addressing challenges in colloidal fabrication of high active mass electrodes. Exceptional adsorption properties of catecholate-type 3,4-dihydroxybenzoic acid (DHBA) molecules are explored for surface modification of Fe3O4 nanoparticles to enhance their colloidal dispersion as verified by sedimentation test results and Fourier-transform infrared spectroscopy measurements. Electrodes prepared in the presence of DHBA show nearly double capacitance at slow charging rates as compared to the control samples without the dispersant or with benzoic acid as a non-catecholate dispersant. Such electrodes with active mass of 40 mg cm−2 show a capacitance of 4.59 F cm−2 from cyclic voltammetry data at a scan rate of 2 mV s−1 and 4.72 F cm−2 from galvanostatic charge–discharge data at a current density of 3 mA cm−2. Experimental results are corroborated by density functional theory (DFT) analysis of adsorption behaviour of DHBA and benzoic acid at the (001) surface of Fe3O4. The strongest adsorption energy (ca. −1.8 eV per molecule) is due to the catechol group of DHBA. DFT analysis provides understanding of the basic mechanism of DHBA adsorption on the surface of nanoparticles and opens the way for fabrication of electrodes with high capacitance.